2006
DOI: 10.1142/s1084946706000350
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Reported Firm Performance by Gender: Does Industry Matter?

Abstract: Business performance results were collected from small business entrepreneurs in one Mid-western state operating in the retail and services industries. These industries account for more than 80 percent of female entrepreneurs' fields of operation. The pattern of reported firm performance between the genders indicated that male entrepreneurs with a high school education reported the highest firm performance scores overall. Female entrepreneurs with a college degree reported the highest firm performance scores a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 24 publications
3
28
1
9
Order By: Relevance
“…Mungaray and Ramírez [19] found that there was a positive relationship between the rate of productivity and the level of education, being this finding congruent with what was found by Swinney et al [20], and they also found that the higher the educational level of the employer is, the higher the performance of companies is.…”
Section: The Characteristics Of Entrepreneurs and Competitivenesssupporting
confidence: 72%
“…Mungaray and Ramírez [19] found that there was a positive relationship between the rate of productivity and the level of education, being this finding congruent with what was found by Swinney et al [20], and they also found that the higher the educational level of the employer is, the higher the performance of companies is.…”
Section: The Characteristics Of Entrepreneurs and Competitivenesssupporting
confidence: 72%
“…As well, Millmore et al (2007), studied gender differences within 360 degree managerial performance evaluations and found that self-evaluations ratings were higher in females than males, although, in their study, this gender difference was not statistically significant (Millmore et al, 2007). Skinner's study of entrepreneurs in the retail trades found that both male and female entrepreneurs reported their performance successful even though male entrepreneurs had a more formal education and generated higher revenues (Swinney, Runyan, & Huddleston, 2006). Siguaw and Honeycutt's (1995) study, supports Skinner's finding, in that they found no significant differences in the performance between male and female salespeople in regards to selling behaviors and attitudes.…”
Section: Gender Differences On Self-evaluation Ratingsmentioning
confidence: 99%
“…This approach allowed the comprehensive and extensive assessment to be done to the entrepreneurs [17,21]. Masuo et al [10] used several proxies to measure the subjective performance of entrepreneurs such as customer satisfaction, personality development, awareness of entrepreneurs and so on.…”
Section: Literature Reviewmentioning
confidence: 99%